Contemptus mundi in cyberspace. - Weissman, Judith (Sewanee Review)
Analyzes several poststructuralist novels. `Aramis or The Love of Technology,' by Bruno Latour; `Beyond Poststructuralism: The Speculations of Theory and Experience of Reading,' by Wendell Harris; `Minutes of the Lead Pencil Club: Pulling the Plug on the Electronic Revolution,' edited by Bill Henderson; Eradication of nature as a category; Worship of computers.